2018
DOI: 10.2147/opth.s178161
|View full text |Cite
|
Sign up to set email alerts
|

Graft rejection-like reactions in the early postoperative period after deep anterior lamellar keratoplasty for keratoconus: a retrospective study

Abstract: BackgroundDeep anterior lamellar keratoplasty (DALK) is indicated to correct high astigmatism in patients with keratoconus (KC) and no evidence of Descemet’s membrane rupture. However, some patients with KC experience graft rejection-like inflammatory reactions within 2 months (usually in the first week) after DALK. The aim of this study was to identify the characteristics and influencing factors of these reactions by reviewing the records of patients who underwent DALK or penetrating keratoplasty (PKP) for KC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In addition, Th1 is downregulated via the Fas ligand in an anterior chamber-associated immune deviation response which leads to an immune-privileged environment [ 22 ]. However, despite this mechanism, immunological rejections do occur, with a higher rate in PK (15–18%) than in anterior lamellar (0–6%) and posterior lamellar (DSEK: 4–9% and DMEK: 1.2%) keratoplasty [ 2 , 11 , 23 25 ]. Still, in keratoplasty, sex or HLA matching is not performed widely.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Th1 is downregulated via the Fas ligand in an anterior chamber-associated immune deviation response which leads to an immune-privileged environment [ 22 ]. However, despite this mechanism, immunological rejections do occur, with a higher rate in PK (15–18%) than in anterior lamellar (0–6%) and posterior lamellar (DSEK: 4–9% and DMEK: 1.2%) keratoplasty [ 2 , 11 , 23 25 ]. Still, in keratoplasty, sex or HLA matching is not performed widely.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported various severities of suture-related complications and graft rejection-like reactions, including suture infiltration and loosening in keratoconus eyes, after keratoplasty [ 16 , 17 ]. Keratoconus eyes with post-PK episodes of VKC reactivation further increased the rate and severity of suture-related problems, such as suture abscess and suture-tract vascularization [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the National Transplantation Registry, currently there is a limited information about indications and outcomes of cor-neal transplantation in Bulgaria. Mostly the outcome measures are based on the graft rejection, which is an important issue but has limited value for evaluation of quality of vision and life of the entire population with ocular transplantation (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%